PENERAPAN STANDARD OPERATIONAL PROCEDURE KARYAWAN ROOM ATTENDANT EVO HOTEL PEKANBARU - Andrea Reza Permana; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Pekanbaru city is a business center in Riau province, therefore many companies invest in Riau province by then placing their big office in Pekanbaru city as their regional head office. This is of course a great opportunity for the city of Pekanbaru because these business activities will require facilities and meeting rooms and lodging. The development of the hospitality industry is currently growing rapidly, apart from being a place to stay, hotels are also used as meeting places. Of course, the hotel industry is growing rapidly, because they offer excellent and dynamic services. The first impression of the whole hotel can be seen from the tidiness and cleanliness of the rooms. Room attendant is a janitor who has responsibility in terms of maintaining cleanliness, tidiness, comfort and completeness of guest rooms at the hotel. A room attendant must be able to manage the rooms that are his duties and responsibilities, because good and bad rooms depend on the quality of the room attendant. Of course, in carrying out their duties, room attendants must work in accordance with directions and regulations which are commonly referred to as standard operating procedures. To improve his quality as a room attendant, a room attendant must comply with standard operating procedures that are used as a reference in carrying out his job of cleaning the room. Because the orientation of the application of standard operating procedures is to provide satisfaction to guests. Therefore, room attendants must be able to carry out their duties as well as possible. Keywords: Standard Operating Procedure, Room Attendant, Housekeeping, Evo Hotel Pekanbaru